The effect of Galanin N-Terminal fragment (1-15) in anhedonia: Involvement of the dopaminergic mesolimbic system. - Millón-Peñuela, Carmelo; Flores-Burgess, Antonio; Gago-Calderón, Belén; García-Durán, Laura; Cantero-García, Noelia; Alén, Francisco; Orio, Laura; Narváez-Bueno, José Ángel; Fuxe, Kjell; Santín-Núñez, Luis Javier; Díaz-Cabiale, Zaida (My University, 2019)
The Galanin N-terminal fragment (1-15) [GAL(1-15)] induces depressant- and anxiogenic-like actions in behavioral tests and these effects were significantly stronger than the ones induced by Galanin. Since anhedonia is a core feature of depression, we have analyzed GAL(1-15) actions in two anhedonic-like behavior tests: saccharin Self-administration and Sucrose Preference test (SPT). In order to investigate whether the effect of GAL(1–15) was associated with the reward circuit, we have studied the GAL(1-15) actions over the mesolimbic system by the expression of the C-Fos, Dat, Vmat2 and Dopamine and GAL receptors genes in VTA and NAc. GAL(1-15) 3nmol significantly decreased the number of reinforcement of saccharin self-administer (p<0.01), while 1nmol lacked effect. GAL(1-15) also significantly reduced the number of reinforcement (p<0.01) compared with GAL. The GALR2 antagonist M871 significantly blocked (p<0.05) the decrease in the number of saccharin reinforcements induced by GAL(1-15). In the SPT, GAL(1-15) decreased the sucrose intake 8 (p<0.05) and 24 hours (p<0.01) after administration. GAL(1-15) at a dose of 3 nmol produced a significant decrease in the mRNA levels of Dat and Vmat2 (p<0.05) and an increase in the D3 receptor (p<0.05) in VTA. In the NAc, GAL(1-15) induced a significant decrease in the expression of C-Fos (p<0.05) mRNA and a significantly increased the mRNA expression of D1 (p<0.05), D2 (p<0.05) and D3 (p<0.05). In the current study, we described for the first time that GAL(1-15) induced a strong anhedonia-like phenotype in several behavioral tests, confirming an important role of this neuropeptide in anhedonia, moreover, the dopaminergic mesolimbic system was described as a key region in GAL(1-15)-mediated action on anhedonia. These results may give the basis for the development of novel therapeutic strategies using GAL(1-15) for treatment of depression and reward-related diseases.
Keywords: Neuropéptidos; Depresión - Tratamiento; Galanina; Anhedonia; Depresión; GAL(1-15); Circuito de Recompensa